Modeling Coastal Environmental Change and the Tsunami Hazard - Weiss, Robert; Dura, Tina; Irish, Jennifer L. (Frontiers in Marine Science, 2022)
The hazard from earthquake-generated tsunami waves is not only determined by the earthquake's magnitude and mechanisms, and distance to the earthquake area, but also by the geomorphology of the nearshore and onshore areas, which can change over time. In coastal hazard assessments, a changing coastal environment is commonly taken into account by increasing the sea-level to projected values (static). However, sea-level changes and other climate-change impacts influence the entire coastal system causing morphological changes near- and onshore (dynamic). We compare the run-up of the same suite of earthquake-generated tsunamis to a barrier island-marsh-lagoon-marsh system for statically adjusted and dynamically adjusted sea level and bathymetry. Sea-level projections from 2000 to 2100 are considered. The dynamical adjustment is based on a morphokinetic model that incorporates sea-level along with other climate-change impacts. We employ Representative Concentration Pathways 2.6 and 8.5 without and with treatment of Antarctic Ice-sheet processes (known as K14 and K17) as different sea-level projections. It is important to note that we do not account for the occurrence probability of the earthquakes. Our results indicate that the tsunami runup hazard for the dynamic case is approximately three times larger than for the static case. Furthermore, we show that nonlinear and complex responses of the barrier island-marsh-lagoon-marsh system to climate change profoundly impacts the tsunami hazard, and we caution that the tsunami runup is sensitive to climate-change impacts that are less well-studied than sea-level rise.